Increased serum piwi-interacting RNAs as a novel potential diagnostic tool for brucellosis - Wang, Cheng; Zhang, Cuiping; Fu, Quan; Zhang, Nan; Ding, Meng; Zhou, Zhen; Chen, Xi; Zhang, Fengmin; Zhang, Chunni; Zhang, Chen-Yu; Wang, Jun-Jun (Frontiers in Cellular and Infection Microbiology, 2022)
Background Piwi-interacting RNAs (piRNAs) have emerged as potential novel indicators for various diseases; however, their diagnostic value for brucellosis remains unclear. This study aimed to evaluate the diagnostic potential of altered serum piRNAs in patients with brucellosis. Methods Illumina sequencing via synthesis (SBS) technology was used to screen the serum piRNA profile in brucellosis patients, and markedly dysregulated piRNAs were confirmed by quantitative real-time polymerase chain reaction (qRT-PCR) assay in two sets from a cohort of 73 brucellosis patients and 65 controls. Results Illumina SBS technology results showed that seven piRNAs were markedly elevated in brucellosis patients compared to normal controls. The seven upregulated piRNAs were further validated individually by qRT-PCR, of which three piRNAs (piR-000753, piR-001312, and piR-016742) were confirmed to be significantly and steadily increased in the patients (> 2-fold, P < 0.01). The area under the receiver operating characteristic (ROC) curve (AUCs) for the three piRNAs ranged from 0.698 to 0.783. The AUC for the three piRNAs combination was 0.772, with a specificity of 86% and a positive predictive value of 90%, respectively. Conclusions The three-piRNA panel identified in this study has potential as a novel blood-based auxiliary tool for brucellosis detection.